Carbon emission allowance allocation with cap and trade mechanism in air passenger transport. (10th September 2016) - Xu, Jiuping; Qiu, Rui; Lv, Chengwei
Abstract: With the rapid development of the aviation industry over the last decade, carbon emissions in air passenger transport have become an increasing concern. By combining the equilibrium strategy with a cap and trade mechanism, this paper proposes a bi-level multi-objective model for carbon emission allowance allocations in air passenger transport, in which a government and airlines are considered as the leader and follower decision makers respectively. Compared with previous studies, this model has the ability to describe the interactions of multiple stakeholders and balance their conflicts. To solve the proposed model, a solution method which integrates an interactive evolutionary mechanism and a fuzzy logic controlled genetic algorithm is developed. Then a numerical example is provided to demonstrate the practical applicability and effectiveness of the method for carbon emission mitigation. Results show that the cap and trade mechanism plays a vital role in mitigating air passenger transport carbon emissions and thus it should be effectively applied to air passenger transport. Results of carbon emission allowance allocations also indicate that the proposed method can provide efficient ways of mitigating carbon emissions for air passenger transport, and therefore assisting decision makers in formulating relevant strategies under multiple scenarios. Highlights: A bi-level model for carbon emission allowance allocation problem is developed. The conflict between air transport demand and emissions reduction is analyzed. The trade-off among different decision makers' profit is analyzed. GA is combined with fuzzy logic controllers to solve the model. The cap and trade mechanism plays a vital role in emission mitigation.